help my inner mathematician to grow

Asked by anmol11_batra | 1st Jul, 2009, 05:27: PM

Expert Answer:

For the quadratic equation to have equal roots.

b2 - 4ac = 0         ...............(1)

In our quadratic equation, (P-Q)2x2+2(P2-Q2)x+k = 0

a = (P-Q)2

b = 2(P2-Q2)

c = k

Substituting the values in eqn (1), we get

(2(P2-Q2))2 = 4 (P-Q). k

4 ((P-Q)(P+Q))2 = 4k (P-Q)

⇒ k = ( P + Q)2 or P2 + Q2 + 2PQ

 

Answered by  | 3rd Jul, 2009, 05:03: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.